Modelling of spall damage in ductile materials and its application to the simulation of the plate impact on copper - 张凤国 周洪强 胡军 邵建立 张广财 洪滔 何斌 (Chinese physics B, 2012)
A statistical model of dynamic spall damage due to void nucleation and growth is proposed for ductile materials under intense loading, which takes into account inertia, the elastic-plastic effect, and initial void size. To some extent, void interaction could be accounted for in this approach. Based on this model, the simulation of spall experiments for copper is performed by using the Lagrangian finite element method. The simulation results are in good agreement with experimental data for the free surface velocity profile, stress record behind copper target, final porosity, and void concentrations across the target. The influence of elastic-plastic effect upon the damage evolution is explored. The correlation between the damage evolution and the history of the stress near the spall plane is also analyzed.